A comparative study of isobaric combustion and conventional diesel combustion in both metal and optical engines. (1st July 2021) - Nyrenstedt, Gustav; Tang, Qinglong; Sampath, Ramgopal; AlRamadan, Abdullah; Ben Houidi, Moez; Cenker, Emre; Magnotti, Gaetano; Johansson, Bengt
Highlights: A detailed picture of the isobaric combustion concept was obtained on an optical engine. High-speed MIE scattering, natural flame imaging, and 10 Hz PLIF and LII were applied. The distribution of fuel vapor and soot in the squish region were visualized. The isobaric combustion cases were compared to the conventional diesel combustion. Multiple injectors are suggested to reduce soot emission and heat loss in isobaric combustion. Abstract: Isobaric combustion is more efficient than isochoric combustion when the peak cylinder pressure is restricted. Recently a double compression expansion engine concept using isobaric combustion was proposed to improve the engine performance. However, the knowledge about the in-cylinder isobaric combustion process is limited. This study investigated isobaric combustion in both metal and optical engines utilizing a centrally placed direct injector and a multiple injections strategy, and the performance and emissions of isobaric combustion and conventional diesel combustion (CDC) were compared. Mie scattering and fuel-tracer planar laser-induced fluorescence (PLIF) were used to visualize the liquid-phase fuel penetration length and fuel distribution under non-reactive conditions, respectively. The natural flame luminosity and spatial soot distribution were measured with high-speed imaging and laser-induced incandescence (LII), respectively. Results demonstrate an increased soot formation in the isobaric cases compared with the CDC case. The successive fuel injection into reacting zones, which induces a locally fuel-rich mixture and less fuel–air mixing, accounts for the high soot emissions in the isobaric combustion. This study further demonstrates that the late injections of the isobaric cases lead to more combustion in the squish zone and near the cylinder walls, which increases the local temperature gradient and may result in more heat losses. There is still room to reduce the heat losses in the isobaric combustion although the total heat loss of the isobaric combustion is lower than the CDC case due to a lower combustion temperature. Multiple injectors are suggested to reduce the soot emissions of the isobaric combustion by spreading the different injections in space.